Migratory Context and Ethnicity in the Entrepreneurial Behavior of Immigrants in their Destination: A Case Study about Okinawans in Brazil (Global Journal of Human-Social Science, 2021)
This study arose from the interest in better understanding the correlations between ethnicity inherent in the contexts of origin, migratory processes and places of destination, to explain the challenges faced and resources used by immigrants to undertake in a sustainable way in the places of destination. Thus, the general objective of the research was to identify among the Okinawan immigrants in Campo Grande/Brazil, on the one hand, the ethnic context given by the historical origin, conditions provided by the migratory process and territory of residence and, on the other, the nature of resources they use in their entrepreneurial practices. This is an exploratory research, supported by collection procedures regarding the researched object and the research subjects. The analysis and interpretation was carried out in a triangulation of contextual, objective and subjective data. The study points to the importance of the culture of origin, family and ethnic social networks in the immigrant's entrepreneurial behavior at the time of their arrival at the destination, as well as the role played by the policies previously planned by countries of origin and destination in expanding opportunities to the greatest extent. sustainability of its ventures.
Keywords: migratory process; ethnicity; entrepreneurial behavior